2010
DOI: 10.1111/j.1467-7652.2009.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast‐derived vaccine antigens confer dual immunity against cholera and malaria by oral or injectable delivery

Abstract: SummaryCholera and malaria are major diseases causing high mortality. The only licensed cholera vaccine is expensive; immunity is lost in children within 3 years and adults are not fully protected. No vaccine is yet available for malaria. Therefore, in this study, the cholera toxin-B subunit (CTB) of Vibrio cholerae fused to malarial vaccine antigens apical membrane antigen-1 (AMA1) and merozoite surface protein-1 (MSP1) was expressed in lettuce and tobacco chloroplasts. Southern blot analysis confirmed homopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
162
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(163 citation statements)
references
References 84 publications
0
162
0
1
Order By: Relevance
“…Equal amounts of total protein along with known amounts of purified bacterial CTB (Sigma) were separated by SDS/PAGE and transferred to a nitrocellulose membrane by electroblotting. Immunoblotting with rabbit anti-CTB primary polyclonal antibody (1:3,000; Sigma) and horseradish peroxidase (HRP) -conjugated donkey anti-rabbit secondary antibody (1:5,000; Southernbiotech) was used for densitometric analysis (12,16,19). A SuperSignal West Pico HRP Substrate Kit (Pierce) was employed for detection of chemiluminescence signal by exposure to film.…”
Section: Regeneration Of Transplastomic Plants and Confirmation Of Trmentioning
confidence: 99%
See 1 more Smart Citation
“…Equal amounts of total protein along with known amounts of purified bacterial CTB (Sigma) were separated by SDS/PAGE and transferred to a nitrocellulose membrane by electroblotting. Immunoblotting with rabbit anti-CTB primary polyclonal antibody (1:3,000; Sigma) and horseradish peroxidase (HRP) -conjugated donkey anti-rabbit secondary antibody (1:5,000; Southernbiotech) was used for densitometric analysis (12,16,19). A SuperSignal West Pico HRP Substrate Kit (Pierce) was employed for detection of chemiluminescence signal by exposure to film.…”
Section: Regeneration Of Transplastomic Plants and Confirmation Of Trmentioning
confidence: 99%
“…Consequently, we and others have been able to produce high levels of several biopharmaceutical proteins and vaccine antigens via the chloroplast system (11,17). Foreign proteins expressed in plant chloroplasts can be efficiently delivered to the immune or circulatory system upon oral delivery when they are fused with the transmucosal carrier cholera toxin B subunit (CTB) (14,18,19).…”
mentioning
confidence: 99%
“…The size of the observed DNA bands was 1,036 bp for the PfCP-2.9 gene and 700 bp for the nptII gene (Van Den Broeck et al, 1985), whereas the negative control showed no band (Figure 1 A and B). The successful expression of malaria antigens, such as AMA1 and MSP1, was reported in lettuce and tobacco (Davoodi-semiromi et al, 2010). However, these genes were individually introduced.…”
Section: Resultsmentioning
confidence: 99%
“…Turpen et al (1995) were the first to report the expression of a malaria antigen in the tobacco plant. Recently published works indicate the expression of antigens against malaria in lettuce and tobacco (Davoodi-semiromi et al, 2010), Arabidopsis thaliana seeds (Lau et al, 2010), and green algae (Dauvillée et al, 2010). The malaria antigens used were AMA1, MSP1 (Dauvillee et al, 2010;Davoodi-semiromi et al, 2010), and MSP1 42 (Lau et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Expression levels have been quite variable, ranging from nearly undetectable to as much as 40% of the total soluble protein (Tregoning et al, 2003;Zhou et al, 2008). However, so far, very few of the chloroplast-produced antigens have successfully been tested in oral vaccination experiments (Tregoning et al, 2003;Davoodi-Semiromi et al, 2010). Moreover, all studies conducted so far have been confined to small experimental animals (usually mice), and the concept of oral vaccination with transplastomic plants still awaits its validation in large mammals and ultimately in humans.…”
Section: Chloroplasts As Bioreactors For Molecular Farmingmentioning
confidence: 99%